BIMBINGAN TAHSIN-TAJWID UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN ANAK-ANAK DI DESA PAGARAN DOLOK KEC. BATANG LUBU SUTAM KAB. PADANG LAWAS - Rahman; Mei Arina Ilmi AS; Sawaluddin Siregar (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2025)
Children are the forerunners of the generation that will become leaders in the future. Leaders are expected to be physically, mentally and spiritually capable. Seeing the increasingly rapid development of the times with the launch of various gadget brands, it is a challenge for society. Because children are made careless of this and forget the importance of studying religious knowledge, especially studying the al-Qur’an. In Pagaran Dolok Village, children are starting to get busy with their gadgets and are lazy about learning the al-Qur’an. With the program offered by the writing team, through the service method of providing teaching through lectures and discussions, it is hoped that it can help children become more proficient and better at reading the al-Qur’an. This program provides significant changes, although slowly, it can be felt by the author himself in particular and children who study in general. Children are starting to get used to the correct pronounciation of letters and know the rules for reciting the verses they read.